Investigating which factors influence consumer’s online purchase intentions: The luxury watch industry - Torres, Madalena Mendes Gonçalves Arez (2022)
The luxury watch industry and all its stakeholders, with a special focus on consumers and retailers, is in need of change due to the digital revolution of the 21st century. Such a unique experience is traditionally made possible by tailored customer service, state of the art stores and displays, which may be jeopardized by the idea of shifting to online channels. Thus, this work aims to investigate which e-commerce characteristics influence consumer’s purchase intentions. Concepts such as trust, website appearance and design, and price awareness were approached. To gain a deep understanding of the aforementioned topics, a quantitative methodology was developed by the means of an online questionnaire and a total of 202 valid responses were obtained. Findings reveal that price awareness, receptiveness to online stores and website trust are the most important predictors of purchase intentions. Additionally, this study explores whether purchase intentions shift given previous online experience.